A Lesson for Covidiots1,2 About Some Contact Induced Borrowing of American English Morphological Processes Into Dutch - Hamans, Camiel (Studia Anglica Posnaniensia, 2021)
This paper discusses morphological borrowing from American-English to Dutch. Three processes of non-morphemic word formation are studied: embellished clipping (Afro from African), libfixing (extracting segments from opaque wordforms such -topia from utopia and -(po)calypse from apocalypse) and blending (stagflation < stagnation + inflation). It will be shown that the borrowing of these processes started with borrowing of English lexical material followed by a process of reinterpretation, which subsequently led to the (re-)introduction of the processes in Dutch. Therefore, the traditional distinction between MAT and PAT borrowing turns out to be inadequate. Instead of a clear-cut difference between lexical and morphological borrowing a borrowing cline will be proposed. The respective ends of this cline are MAT and PAT.